2021
DOI: 10.1186/s12348-021-00255-1
|View full text |Cite
|
Sign up to set email alerts
|

Fungal keratitis caused by Pseudallescheria boydii: clinical and mycological characteristics

Abstract: Background Pseudallescheria keratitis is rare but important type of fungal keratitis because of the inherently resistance of the organism to many existing antifungal agents. Methods Slit-lamp and confocal microscopy were used for clinical examinations. Fungal isolates were identified based on morphological characteristics and DNA sequence of the internal transcribed spacer region (ITS). In vitro antifungal susceptibility testing for fungal isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
1
0
2
Order By: Relevance
“…En cuanto a las especies de Scedosporium son más inusuales de encontrar entre los causantes de queratitis [ 6 ]. El primer caso de queratitis por Scedosporium fue descrito en 1955 [ 7 ] y continúa siendo inusual. Dentro de dicho género, las especies con mayor relevancia clínica para el hombre son: S. apiospermum, S. boydii, S. aurantiacum, S. dehoogii y S. minutisporum [ 8 ].…”
unclassified
See 1 more Smart Citation
“…En cuanto a las especies de Scedosporium son más inusuales de encontrar entre los causantes de queratitis [ 6 ]. El primer caso de queratitis por Scedosporium fue descrito en 1955 [ 7 ] y continúa siendo inusual. Dentro de dicho género, las especies con mayor relevancia clínica para el hombre son: S. apiospermum, S. boydii, S. aurantiacum, S. dehoogii y S. minutisporum [ 8 ].…”
unclassified
“…Sigue habiendo un alto porcentaje de fracaso terapéutico; el escenario futuro podría mejorar con la incorporación de nuevas técnicas diagnósticas y el desarrollo de nuevos fármacos. El microscopio confocal es una técnica no invasiva, subjetiva y útil en el caso de queratitis fúngicas y por Acanthamoeba [ 7 , 17 ]. Por otro lado, en el laboratorio de microbiología, las técnicas de biología molecular, presentan una alta sensibilidad y especificidad, permitiendo acortar el tiempo de respuesta a 4-8 horas frente a los 15 días del cultivo [ 4 ].…”
unclassified
“…In Iran, several human scedosporiosis have been reported [20][21][22][23][24][25][26]. These isolates have been identified based on the morphological and molecular methods that triggered illness through S. boydii, S. apiospermum, S. aurantiacum, and S. ellipsoideum, which are the most prevalent species described in the literature [20][21][22][23][24][25][26]. The current study reported the presence of S. dehoogii in paddy field soil in Iran for the first time.…”
mentioning
confidence: 99%